Cultural Translation Theory and Its Application in Oil-Paper Umbrella Design - Yanfei, Tang; Wai Yie, Leong (INTI International University, 2025)
This study explores the transformation of the oil-paper umbrella, an intangible cultural heritage,through cultural translation theory in modern creative design. By analyzing the cultural symbols at material, behavioral, and spiritual levels, products like earrings, necklaces, and pens were designed. The findings provide practical references for the innovative transformation of cultural heritage.